PENGEMBANGAN BAHAN AJAR TEMA V EKOSISTEM BERORIENTASI HOTS PADA SISWA KELAS V SEKOLAH DASAR - Andri Valen; Cahyo Dwi Andita; Titi Maharani (Jurnal Muara Pendidikan, 2023)
This research is motivated by students' difficulties in solving problems that arise related to learning science. The goal to be achieved in this study is to know the feasibility of HOTS-oriented ecosystem V-theme teaching materials that are valid, practical, and effective for fifth-grade elementary school students. The results of the practicality trial obtained data from the small group trial of 92.78% and the teacher practicality trial of 90.48% with a very practical classification. Therefore, the total of the data obtained has a percentage of 91.63% with a very practical classification. The effectiveness test was carried out on fifth-grade students at SD Negeri 1 Sumber Harta, which consisted of 22 students. The average pretest score obtained by students is 44.09. While the average post-test score obtained by students is 85.09. Based on the results of the data from the two tests carried out, the level of effectiveness of teaching materials based on N-Gain is 0.73 with a high classification. So it can be concluded that HOTS-oriented teaching materials are declared effective and appropriate to be used to assist students in learning activities at school.